2016
DOI: 10.7567/jjap.55.121301
|View full text |Cite|
|
Sign up to set email alerts
|

Proximity gettering of C3H5 carbon cluster ion-implanted silicon wafers for CMOS image sensors: Gettering effects of transition metal, oxygen, and hydrogen impurities

Abstract: A new technique is described for manufacturing silicon wafers with the highest capability yet reported for gettering transition metallic, oxygen, and hydrogen impurities in CMOS image sensor fabrication. It is demonstrated that this technique can implant wafers simultaneously with carbon and hydrogen elements that form the projection range by using hydrocarbon compounds. Furthermore, these wafers can getter oxygen impurities out-diffused from the silicon substrate to the carbon cluster ion projection range dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 31 publications
0
88
0
Order By: Relevance
“…In our previous study , it was found that a carbon cluster ion implanted silicon wafer had three characteristics for high performance of advanced CMOS image sensors. First, a carbon cluster ion projection range has high gettering ability of metallic impurities during heat treatment . Second, this projection range also has a diffusion barrier effect for oxygen impurities out‐diffusing to the device active regions from the CZ grown silicon wafer substrate .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study , it was found that a carbon cluster ion implanted silicon wafer had three characteristics for high performance of advanced CMOS image sensors. First, a carbon cluster ion projection range has high gettering ability of metallic impurities during heat treatment . Second, this projection range also has a diffusion barrier effect for oxygen impurities out‐diffusing to the device active regions from the CZ grown silicon wafer substrate .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Second, this implanted region of carbon clusters also has a barrier effect on oxygen impurities diffusing out from the Si wafer bulk. 14,15) Third, a passivation effect on process-induced defects is expected owing to the hydrogen in the carboncluster ions trapped in the implanted region during the device fabrication process. 16,18) However, the formation behavior of the implantation defects considered to be the gettering sinks in the implanted region around the projection range of the carbon clusters is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that carbon-cluster-ion-implanted epitaxial wafers have three characteristics useful for achieving high-performance advanced CMOS image sensors. [14][15][16] First, the silicon surface within the projection range of carbon clusters has a high gettering capability for metallic impurities. [14][15][16] Second, this implanted region of carbon clusters also has a barrier effect on oxygen impurities diffusing out from the Si wafer bulk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations